Efficiency of Sports Leagues - The Economic Implications of Having Two Leagues in the Indian Cricket Market - Vig, Arun (2008)
Worldwide more and more money is being invested in sports teams and professional sports leagues. There are numerous sports that are popular in different parts of the world. In the United States, its American Football, in Europe and UK it is Football (soccer); in the Indian sub-continent and Australia it is Cricket that attracts the largest crowds.